Evektivitas metode pembelajaran berbasis kisah nabi dalam membentuk karakter anak usia dini di tk alfatah batam - Sephianty, ridhaananda (Hamka Ilmu Pendidikan Islam, 2025)
Character education in early childhood faces serious challenges due to modernenvironmental influences and the decline of moral value internalization in children’s daily lives.This study aims to examine the role of storytelling methods based on prophetic stories in shapingmoral and religious character in early childhood education at TK Al-Fatah Batu Aji. This researchemploys a qualitative descriptive approach through a thematic analysis of prophetic narratives inthe Qur’an, particularly the stories of Prophet Musa, Prophet Ibrahim, Prophet Muhammad, andProphet Yunus. The findings reveal that prophetic stories contain strong character educationvalues, including monotheism, religiosity, honesty, patience, responsibility, self-reflection, andcompassion. Storytelling is proven to be effective because it delivers moral values in an engaging,contextual, and developmentally appropriate manner, enabling children to better understand andemulate positive behaviors. Therefore, storytelling based on prophetic narratives can beimplemented as an effective learning strategy to strengthen character education in early childhoodwithin an Islamic educational framework.